2012
DOI: 10.1007/s00347-012-2732-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapie der retinalen angiomatösen Proliferation im Stadium III

Abstract: Retinal angiomatous proliferation (RAP) is a subtype of exudative age-related macular degeneration which is characterized by an intraretinal origin of the lesion and a particularly poor prognosis. In this retrospective case study 33 eyes from 33 patients with stage III RAP lesions were included and initially treated with 3 intravitreal injections of 0.5 mg ranibizumab at monthly intervals. Criteria for extended treatment were visual deterioration, fresh bleeding, residual fluid or increase of the central retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In our results, treatment prognosis differs according to the clinical stage of RAP during the 12 months. In several recent reports, intravitreal ranibizumab monotherapy was given mostly to patients with stage II and III RAP lesions [ 28 , 29 ]. Parodi et al [ 30 ] demonstrated that both ranibizumab and bevacizumab showed similar efficacy in stage I and II RAP.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, treatment prognosis differs according to the clinical stage of RAP during the 12 months. In several recent reports, intravitreal ranibizumab monotherapy was given mostly to patients with stage II and III RAP lesions [ 28 , 29 ]. Parodi et al [ 30 ] demonstrated that both ranibizumab and bevacizumab showed similar efficacy in stage I and II RAP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the intravitreal delivery of pharmacological agents has been used for treatment of retinopathies and vitreous diseases. Diverse therapeutic molecules are delivered intravitreally in ophthalmological practice, including the viral vectors, peptides, proteins, and nucleic acids (Maier et al., 2013 ; Hartman & Kompella, 2018 ).…”
Section: Introductionmentioning
confidence: 99%